NO way! Nasal nitric oxide measurement in infants. Issue 6 (21st June 2018) - Lucas, Jane S.; Walker, Woolf T.
Primary ciliary dyskinesia (PCD) generally causes symptoms from the first weeks of life, but diagnosis is usually delayed for years or can be missed altogether. Referral for diagnostic testing is often late because key symptoms, such as wet cough, chronic rhinitis and recurrent upper and lower respiratory tract infection, are non-specific. An international survey of patients reported that 37% had >40 visits to medical professionals due to PCD-related symptoms before being referred for diagnostic testing [1]. Approximately 50% of children with PCD have situs inversus, a rare condition in the general population, and it is therefore not surprising that these patients are investigated earlier. A European survey found that age of diagnosis was at 3.5 years in those with situs inversus and 5.8 years in children with normal situs [2]. Assuming a prevalence of 1 in 10 000 [3], we expect ∼1180 diagnosed children in England (childhood population ∼11.8 million); however, there are currently only ∼340 children in the National Paediatric PCD Service. This highlights a huge proportion of undiagnosed patients even in a country with a national PCD service [4]. This is in stark contrast to cystic fibrosis (CF) where neonatal screening programmes ensure that diagnosis occurs in early infancy in many countries, with positive impact on clinical outcome [5]. Young children with PCD have similarly impaired forced expiratory volume in 1 s to children with CF [6], and require multidisciplinary treatment. Early diagnosis facilitates a management plan, including regular airway clearance physiotherapy, surveillance for airway pathogens with treatment of respiratory exacerbations, genetic counselling for families, audiology monitoring and management of conductive hearing loss [7, 8]. We expect that early diagnosis would delay respiratory decline and ensure specialist treatment of ear, hearing and nasal issues, thereby optimising health, psychological, social and educational outcomes. Nasal nitric oxide (NO) measurement is feasible in infants, potentially allowing earlier diagnosis of primary ciliary dyskinesia http://ow.ly/9K0a30kpcZU